Renal vascular resistance is increased in patients with kidney transplant - Päivärinta J; Oikonen V; Räisänen-Sokolowski A; Tolvanen T; Löyttyniemi E; Iida H; Nuutila P; Metsärinne K; Koivuviita N (BMC, 2022)
Background Despite improvement in short-term outcome of kidney transplants, the long-term survival of kidney transplants has not changed over past decades. Kidney biopsy is the gold standard of transplant pathology but it's invasive. Quantification of transplant blood flow could provide a novel non-invasive method to evaluate transplant pathology. The aim of this retrospective cross-sectional pilot study was to evaluate positron emission tomography (PET) as a method to measure kidney transplant perfusion and find out if there is correlation between transplant perfusion and histopathology. Methods Renal cortical perfusion of 19 kidney transplantation patients [average time from transplantation 33 (17-54) months; eGFR 55 (47-69) ml/min] and 10 healthy controls were studied by [(15) O]H2O PET. Perfusion and Doppler resistance index (RI) of transplants were compared with histology of one-year protocol transplant biopsy. Results Renal cortical perfusion of healthy control subjects and transplant patients were 2.7 (2.4-4.0) ml min(- 1) g(- 1) and 2.2 (2.0-3.0) ml min(- 1) g(- 1), respectively (p = 0.1). Renal vascular resistance (RVR) of the patients was 47.0 (36.7-51.4) mmHg mL(- 1)min(- 1)g(- 1) and that of the healthy 32.4 (24.6-39.6) mmHg mL(- 1)min(-1)g(-1) (p = 0.01). There was a statistically significant correlation between Doppler RI and perfusion of transplants (r = - 0.51, p = 0.026). Transplant Doppler RI of the group of mild fibrotic changes [0.73 (0.70-0.76)] and the group of no fibrotic changes [0.66 (0.61-0.72)] differed statistically significantly (p = 0.03). No statistically significant correlation was found between cortical perfusion and fibrosis of transplants (p = 0.56). Conclusions [(15) O]H2O PET showed its capability as a method in measuring perfusion of kidney transplants. RVR of transplant patients with stage 2-3 chronic kidney disease was higher than that of the healthy, although kidney perfusion values didn't differ between the groups. Doppler based RI correlated with perfusion and fibrosis of transplants.